The Onset of Pandemic-Induced Isolation in Soup Kitchens in La Matanza, Buenos Aires Province: Between Words and Images - Faracce Macia, Constanza (2025)
In the context of the pandemic, the State has assisted the population through multiple interventions, among which are the resources provided and the protocols destined to soup kitchens, which have played a central role in alleviating the socioeconomic consequences since the beginning of the COVID-19 pandemic. This article seeks to identify the transformations in these spaces La Matanza (Argentina) during the pandemic. From a virtual ethnography on Facebook, textual narratives and images, in societies crossed by information technologies, establish new dynamics of social exchange, which allow us to describe the transformations implied by the beginning of isolation in these spaces.